Experience, Knowledge, and Risk Perception Among Adventure Tourism Workers in Yogyakarta - Ahmad Afif Mauludi; Rini Puspita Dewi; Muhammad Azrin Karim; Tri Arini; Dwina Anggraini; Tia Nurhidayanti; Arif Sulfiantono (Lembaga Penelitian Publikasi dan Pengabdian Masyarakat LSPR, 2026)
This study examined occupational health and safety (OHS) risk perception and its influencing factors among adventure tourism workers in Yogyakarta, Indonesia. A cross-sectional, quantitative design was used with data collected via self-administered online questionnaire from 114 workers aged 17 to 58 years. Non-parametric tests were applied: Spearman's Rho, Kendall's Tau, Mann-Whitney U, and Kruskal-Wallis H. Workers rated most hazards at the